Dianetics the original thesis - Hubbard, L. Ron (La Fayette Ron), 1911-1986 (Bridge Publications, Inc., 2007)
According to the publisher, this book presents the bedrock foundation of Dianetic discoveries : the original axioms, the dynamic principle of existence, the anatomy of the analytical and reactive mind, the dynamics, the tone scale, the auditor's code, and the first description of a clear. Also included is a description of the author's beliefs regarding "auditing"